2001
DOI: 10.1021/ja003966j
|View full text |Cite
|
Sign up to set email alerts
|

Electron Self-Exchange in the Solid-State: Cocrystals of Hydroquinone and Bipyridyl Triazole

Abstract: Solid-state voltammetry, spectroscopy, and microscopy studies have been used to probe the proton and electron conductivity within a self-assembled cocrystal, HQBpt. This crystallographically defined material contains 3,5-bis(pyridin-2-yl)-1,2,4-triazole, HBpt, dimers that are pi-stacked and hydrogen bonded to 1,4-hydroquinone, H(2)Q, in a herringbone arrangement. When deposited onto platinum microelectrodes, the cocrystal exhibits a well-defined voltammetric response corresponding to oxidation of H(2)Q to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Comparing with those spectra in CHCl 3 , the absorption and emission reveal red‐shift result from the protonation of imine nitrogen in DIOXD, OXD, or TAZ fluorophores. The protonation usually leads to change in optical properties such as fluorescence quench, absorption or emission shift, and spectra broadening 42–44. Monkman et al had demonstrated that the protonation of nitrogen has an important structural effect: intramolecular hydrogen bonding to the adjacent oxygen atom in the alkoxy substituent planarizes backbones of the molecules, which leads to red‐shifts of both absorption and emission spectra 34.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing with those spectra in CHCl 3 , the absorption and emission reveal red‐shift result from the protonation of imine nitrogen in DIOXD, OXD, or TAZ fluorophores. The protonation usually leads to change in optical properties such as fluorescence quench, absorption or emission shift, and spectra broadening 42–44. Monkman et al had demonstrated that the protonation of nitrogen has an important structural effect: intramolecular hydrogen bonding to the adjacent oxygen atom in the alkoxy substituent planarizes backbones of the molecules, which leads to red‐shifts of both absorption and emission spectra 34.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SSEAC methods provide information on the reactivity of solid compounds, both from a thermodynamic as well as from a kinetic point of view. Available examples include nucleation, growth, redistribution, and dissolution processes in fullerenes [165] and metal-organic frameworks [159,160], electrochemical lattice reconstruction in hexacyanometallates [166], electron self-exchange in the solid state [167], and formation of solid inclusion complexes [168].…”
Section: Notementioning
confidence: 99%
“…Additionally, an electrocatalytic effect exerted by the solid materials on selected electrochemical processes can be utilized to obtain information on the composition of solids [166][167][168][169][210][211][212], including organic and pharmaceutically active compounds [213][214][215][216][217]. Here, the electrochemical oxidation/reduction process of an auxiliary species in solution phase is catalytically enhanced at sample-mod- ified electrodes relative to that occurring at unmodified electrode.…”
Section: Analytical Strategiesmentioning
confidence: 99%
“…Previously researchers [44] 2) where n is the number of electrons involved, D APP is the apparent diffusion coefficient describing homogeneous charge transport through the film, C EFF is the effective concentration of the Os 2+ centres in the film, and r is the radius of the microelectrode.…”
Section: Bulk Concentration and Homogeneous Charge Transportmentioning
confidence: 99%